Efektivitas Science Technology Society Disertai Permainan Imajinatif terhadap Sikap Peduli Lingkungan Siswa Sekolah Dasar pada Mata Pelajaran IPA - Saiful Bahri; Rina Purnama Sari; Yanti Susanty (STKIP Taman Siswa Bima, 2023)
This study aims to determine the effectiveness of Science Technology Society accompanied the caring attitude of imaginative play environment of elementary school students on IPA. This research included ine population were all students of SDN Langsa Lama. The sampling technique used was cluster random sampling, in order to obtain class 3A as an experimental group and class 3B as the control group. Data collection techniques use essay teScience Technology Society, observation sheets, as well as their academic papers. Hypothesis testing is done by using test-t. this research concluded that the integration of Science Technology Society accompanied the Effective imaginative play environment caring attitude of elementary school students in science subjects